Papaveraceae - EGAN, PAUL (Royal Botanic Garden Edinburgh, 2011)
The Internet-accessible account of Papaveraceae for the Flora of Nepal includes all native and fully naturalized species, detailed taxonomic information and distribution maps, and brief references to agricultural and horticultural plants as appropriate. The account covers the genera Argemone, Cathcartia, Papaver, Meconopsis and Dicranostigma.
Flora of Nepal, Volume 3
PUBLISHED
Keywords: Flora of Nepal; Himalayan poppy; Meconopsis; Nepal poppy; Taxonomy; Distribution; Central Himalaya